2019
DOI: 10.1021/acs.jafc.8b06785
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Biological Effects of 2-O-β-d-Glucopyranosyl-carboxyatractyligenin from Green Coffee in Caenorhabditis elegans

Abstract: Targeted analysis of Coffea arabica and Coffea canephora green coffees (total sample size n = 57) confirmed 2-O-β-d-glucopyranosyl-carboxyatractyligenin (6) as the quantitatively dominating carboxyatractyligenin derivative. Its abundance in Arabicas (2425 ± 549 nmol/g, n = 48) exceeded that in Robustas (34 ± 12 nmol/g, n = 9) roughly by a factor of 70. Coffee processing involving heat (e.g., steam treatment and decaffeination) reduced concentrations of 6 and increased those of the decarboxylated derivative. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…2- O- β - d -Glucopyranosyl-carboxyatractyligenin was previously identified as the major carboxyatractyligenin derivative in green coffee . On the other hand, the carboxy-derivative could not be detected in roasted coffee samples but instead contained atractyligenin at levels ranging from 225 to 279 nmol/g .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…2- O- β - d -Glucopyranosyl-carboxyatractyligenin was previously identified as the major carboxyatractyligenin derivative in green coffee . On the other hand, the carboxy-derivative could not be detected in roasted coffee samples but instead contained atractyligenin at levels ranging from 225 to 279 nmol/g .…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, the carboxy-derivative could not be detected in roasted coffee samples but instead contained atractyligenin at levels ranging from 225 to 279 nmol/g . This showed that 2- O- β - d -glucopyranosyl-carboxyatractyligenin was initially present in the raw coffee, but was subsequently degraded during the roasting process, resulting in decarboxylation to generate atractyligenin, 2- O- β - d -glucopyranosylatractyligenin, and 3′- O-β- d -glucopyranosyl-2′- O- isovaleryl-2β-(2-desoxy-atractyligenin)-β- d -glucopyranoside. , …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…An overview is given in Table 1. The main assays used to study C. elegans comprise brood-size (number of eggs producedtotal progeny), growth and reproduction, life-span and oxidative stress (Liao 2018;Piechulek and Mikecz 2018;Moyson et al 2019;Spanier et al 2019;Wang et al 2020). Compared to rats and rabbits, in a large-scale evaluation of the developmental toxicity of chemicals in the ToxCast TM library, C. elegans was found to be very accurate for predicting developmental toxicity.…”
Section: Toxicokinetics In Caenorhabditis Elegansmentioning
confidence: 99%